Proceedings of the III the Republican Youth Scientific-practical Conference “i-Customs.by” - (:unkn) unknown (BNTU, 2021)
Materials that deal with topical theoretical and practical issues of customs regulation, border security and international trade are presented in the collection of scientific articles of the III Republican Youth Scientific-practical Conference “i- Customs.by”. This collection of articles is addressed to employees of the customs authorities, graduate students, undergraduates, students, professors, as well as to all interested persons studying the problems of international trade and customs.
Minsk, 5 May 2020